Zack's alligator - Mozelle, Shirley; Watts, James, 1955- (New York : HarperCollins, 1989)
When Zack soaks his new alligator keychain in water, it grows into a full-sized and fun-loving alligator.
2.4.
2.4
K-3
Keywords: Alligators -- Juvenile fiction; Alligators -- Fiction; Alligators -- Fiction; Readers (Elementary).